Aplikasi E-Culture Berbasis Android Sebagai Upaya Meningkatkan Nilai Sebuah Kebudayaan - Karim, Abdul Abd; Hudawi, Ahmad (Journal of Advanced Research in Informatics, 2023)
Abstract E-culture is a concept that describes the idea that technology and the internet significantly shape the way we interact, behave, think and communicate as humans in a social environment by utilizing information and communication technology. Culture (culture) can be formed from several elements, namely religious and political systems, customs, language, clothing/appearance, works of art, and others. The e-culture referred to in this study is an activity of local wisdom tradition or culture which was originally carried out manually (recorded on paper) and then converted into digital records. One of the local wisdoms that is the focus of this research is the ulem-ulem culture which is built based on Android. Keywords: E-Culture, technology, Ulem-ulem